PENGARUH TENAGA KERJA DAN PENGELUARAN PEMERINTAH TERHADAP PRODUK DOMESTIK REGIONAL BRUTO SEKTOR PERTANIAN DI KAWASAN TIMUR INDONESIA - Nadia Wahyuni Himari; Sri Indriyani Suwandi Dai; Sri Endang Saleh; Ivan Rahmat Santoso (IDEI: Jurnal Ekonomi & Bisnis, 2024)
Labor absorption and government expenditure were closely related to the agricultural sector's gross regional domestic product (GRDP). This research aimed to analyze the influence of labor and government expenditure on GRDP in the agricultural sector in eastern Indonesia in 2017–2021. This research used a multiple linear regression analysis approach for panel data with a fixed effect model (FEM). The data used in this research were secondary data obtained from Statistics Indonesia and the Directorate General of Financial Balance (DJPK) of the Ministry of Finance of the Republic of Indonesia, obtained from 13 provinces in Indonesia. The results of this research indicated that (1) labor in the agricultural sector possessed a positive and insignificant effect on GRDP in the agricultural sector, meaning that every one percent increase in labor in the agricultural sector could increase GRDP in the agricultural sector in eastern Indonesia, but labor in the agricultural sector was not yet able to explain in real terms; (2) government spending in the agricultural sector possessed a positive and significant effect on the GDP of the agricultural sector, meaning that for every one Rupiah increase in government spending in the agricultural sector could increase the GDP value of the agricultural sector. This study provides practical implications for the government as a policymaker regarding labor and expenditure, especially in the agricultural sector.    Penyerapan tenaga kerja dan pengeluaran pemerintah sangat erat kaitannya dengan Produk Domestik Regional Bruto (PDRB) sektor pertanian. Penelitian ini bertujuan untuk menganalisis pengaruh tenaga kerja dan pengeluaran pemerintah pada PDRB sektor pertanian di Kawasan Timur Indonesia tahun 2017–2021. Penelitian ini menggunakan pendekatan analisis regresi linear berganda data panel dengan fixed effect model (FEM). Data yang digunakan dalam penelitian ini adalah data sekunder yang bersumber dari Badan Pusat Statistik dan Direktorat Jenderal Perimbangan Keuangan (DJPK) Kementerian Keuangan Republik Indonesia yang diperoleh dari 13 provinsi di Indonesia. Hasil penelitian ini menunjukan bahwa (1) tenaga kerja sektor pertanian berpengaruh positif dan tidak signifikan pada PDRB sektor pertanian, artinya setiap peningkatan satu persen tenaga kerja sektor pertanian, maka dapat meningkatkan PDRB sektor pertanian di Kawasan Timur Indonesia, akan tetapi tenaga kerja sektor pertanian belum mampu menjelaskan secara nyata; (2) pengeluaran pemerintah di sektor pertanian berpengaruh positif dan signifikan pada PDRB sektor pertanian, artinya setiap peningkatan sebesar satu Rupiah pengeluaran pemerintah di sektor pertanian, maka dapat meningkatkan nilai PDRB sektor pertanian. Studi ini memberikan implikasi praktis bagi pemerintah selaku pengambil kebijakan terkait tenaga kerja dan pengeluaran khususnya di sektor pertanian.